Development experiences in Estonia, Latvia, and Lithuania after 2004 - Assistant Lecturer Hind Ahmed Abd (Tikrit Journal For Political Science, 2023)
This study examines the developmental experiences in the Baltic countries, namely Estonia, Latvia, and Lithuania, after 2004. Following their accession to the European Union, these countries underwent significant transformations in the fields of economy, population, and culture. The study aims to analyze the developmental changes in these countries and evaluate their impact on the assets of the population, their languages, and the population's developmental indicators and wealth. The analysis revolves around the key aspects of development in these countries after 2004. The influence of these transformations on the assets of the population and their languages will be studied, with a focus on demographic changes and linguistic diversity. Additionally, the study will analyze population development indicators such as population growth rate, fertility rate, and mortality rate, to understand the population shifts in those countries.